(untitled) (Medico Legal Update, 2020)
Lip print is an anatomical character of the human lips. In forensic identification, lip print patterns can lead us to important information and helps in person’s identification. The grooves present on human lips (Sulci labiorum) are unique to each person and can be used to determine identity. Fingerprints, post-mortem reports and of late, DNA fingerprinting, have been successful in person identification in the field of forensic science. Just as in these method, lip prints can be instrumental in identifying a person positively and can be used to verify the presence or absence of a person at the scene of crime . Cheiloscopic techniques have an equal value in relation to other types of forensic evidences for personal identificationMaterial & method:- The study was conducted on 100 students of age group 18-25 yrs. Lip stick was applied on each individual and the lip-print was obtained on a paper. The lip impression patterns were studied, classified and recorded using magnifying lens with light.Result:- Lip patterns are unique for the individual and no two patterns are identical to each other . In study population,Type III pattern was most common in male while In females predominant pattern was type I. Thus in medico legal case, due to clear differentiation in sexes it is easy to identify person and gender. Conclusion:- Cheiloscopy can be reliable method for personal identification and gender dimorphism.